MARKETING STRATEGIES OF POLISH BANKS – EVALUATION ATTEMPT - Wojciech Grzegorczyk (Polityki Europejskie, Finanse i Marketing)
This article attempts to assess the marketing strategies implemented by banks in Poland, especially after the Polish accession to the EU. It is a result of the analysis of secondary sources and the author’s own primary research (project funded by the State Committee for the Scientific Research). The author formulates the hypothesis that since 2003 marketing activities of banks and the effects of these activities have been systematically improving. The marketing strategies of banks in Poland, especially after accession to the EU can be described as professional. The expenditure on marketing research has been steadily growing. New innovative banking products have been widely introduced. Banks set prices for their products not only based on cost but also on the prices of competing products and, increasingly, demand forecasts. Various forms of distribution of banking products have developed, Internet channel being the one of the most intensely growing. Promotional activities were carried out professionally. It can be assumed that the marketing strategies of banks were one of the main factors positively influencing their financial performance and competitive position in the market.